Suria Gading Sdn Bhd (Solar Light) / Shahrul Nizam Ahmad... [et al.] - Ahmad, Shahrul Nizam; Mohamed Samsa, Wan Salmi; Wahid, Norwahida; Azmi, Siti Hajar (2003)
Suria Gading Sdn Bhd is a company which sells and services solar lights products. Solar light products are using sun as the source of energy to create light. Instead of using the electric lamp as source of light, solar light will give the same but better in quality, less cost, weather proof and lot more advantages which will satisfy the needs of modern life. We are confident that people will be attracted to use solar lights as source of lights because now is the era of technology and people in Malaysia are always ready to use the latest technology in their lives. This kind of business also is still new in and we will be the first to run this business in the state of Kedah. We are ready to introduce solar light products in the northern part of Malaysia and we are aiming to build the business all over Malaysia. As we know that sun is the natural source, the gift from Allah is created to give the benefits to human. We are confident that this product will satisfy the human needs at its best.